2018
DOI: 10.1101/391482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reactive Centre Loop Dynamics and Serpin Specificity

Abstract: Serine proteinase inhibitors (serpins), typically fold to a metastable native state and undergo a major conformational change in order to inhibit target proteases. However, conformational labiality of the native serpin fold renders them susceptible to misfolding and aggregation, and underlies misfolding diseases such as α1-antitrypsin deficiency. Serpin specificity towards its protease target is dictated by its flexible and solvent exposed reactive centre loop (RCL), which forms the initial interaction with th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…All serpins share a conserved tertiary structure made of three β-sheets, eight or nine α-helices and a reactive centre loop (RCL), which contains 17 amino acids and is located between the A and C β-sheets (11). The RCL is the main action site located in the protease recognition domain close to the C-terminus of serpin (12) and determines the specificity of serpin inhibitory functions (13,14). Previous research has demonstrated that there are two types of serpin inhibitory mechanisms, termed the inhibitory pathway and the substrate pathway (Fig.…”
Section: Serpin Superfamilymentioning
confidence: 99%
“…All serpins share a conserved tertiary structure made of three β-sheets, eight or nine α-helices and a reactive centre loop (RCL), which contains 17 amino acids and is located between the A and C β-sheets (11). The RCL is the main action site located in the protease recognition domain close to the C-terminus of serpin (12) and determines the specificity of serpin inhibitory functions (13,14). Previous research has demonstrated that there are two types of serpin inhibitory mechanisms, termed the inhibitory pathway and the substrate pathway (Fig.…”
Section: Serpin Superfamilymentioning
confidence: 99%
“…89,90 Replacing conserpin RCL residues P7-P1 0 with P7-P2 0 from α 1 -AT, so that the RCL length and identity were closer to a natural serpin, improved SI values although complexes continued to dissociate faster than wild type α 1 -AT. 90,91 Interestingly, the protein remained unable to efficiently inhibit the primary cognate proteinase neutrophil elastase, which may be due to changes in RCL structural dynamics and the modified electrostatic potential of the serpin body. 91 These studies further stress the important balance between the inhibitory properties of α 1 -AT and its stability, which remain challenging engineering independent of one another.…”
Section: Altering Stabilitymentioning
confidence: 99%
“…90,91 Interestingly, the protein remained unable to efficiently inhibit the primary cognate proteinase neutrophil elastase, which may be due to changes in RCL structural dynamics and the modified electrostatic potential of the serpin body. 91 These studies further stress the important balance between the inhibitory properties of α 1 -AT and its stability, which remain challenging engineering independent of one another.…”
Section: Altering Stabilitymentioning
confidence: 99%
See 2 more Smart Citations